Hello, Janice : The Wartime Letters of Henry Giles - Giles, Henry, 1916-1986 (Book collections on Project MUSE., 2015)
The novels of Janice Holt Giles grew in part from her marriage to Kentuckian Henry Giles. That union and the couple's settling near Henry's boyhood home in Kentucky provided the source and inspiration for Janice's earliest books and influenced much of her later writing. Hello, Janice tells the story of how their marriage came about.